Towards an atomic-scale understanding of oxide film in the Ti powder surface. (15th March 2022) - Tao, Qiying; Ding, Wangwang; Chen, Gang; Qu, Xuanhui; Qin, Mingli
Abstract: In-depth understanding of the nature of oxide film in the Ti powder surface was investigated at an atomic scale in terms of quantitative composition, spatial distribution and thickness. The oxide film consists of TiO2, Ti2 O3 and TiO with a continuous spatial distribution, acquired from the atomic ratio of O/Ti by EELS and APT. Composition and structure of the oxide film were thoroughly explored based on the oxygen-atomic diffusion theory and thermodynamic analysis to uncover the oxidation mechanism of the Ti powders. This study opens opportunities to gauge the powder properties, optimize the subsequent processing, and improve the final performance. Graphical abstract: Image, graphical abstract